Assessing Automatic Approach-Avoidance Behavior in an Immersive Virtual Environment - Degner, Juliane; Steep, Lea; Schmidt, Susanne; Steinicke, Frank (Frontiers in Virtual Reality, 2021)
The use of virtual reality (VR) promises enormous potential for studying human behavior. While approach and avoidance tendencies (AAT) have been explored in various areas of basic and applied psychology, such as attitude and emotion research, basic learning psychology, and behavior therapy, they have rarely been studied in VR. One major focus of AAT research is to understand the psychological mechanisms underlying automatic behavioral tendencies towards and away from positively or negatively evaluated stimuli. We implemented a whole-body movement stimulus-response compatibility task to explore approach-avoidance behavior in an immersive virtual environment. We chose attitudinal stimuli - spiders and butterflies - on which people widely agree in their general evaluations (in that people evaluate spiders negatively and butterflies positively), while there is still substantial inter-individual variance (i.e., the intensity in which people dislike spiders or like butterflies). We implemented two parallel approach-avoidance tasks, one in VR, one desktop-based. Both tasks revealed the expected compatibility effects that were positively intercorrelated. Interestingly, however, the compatibility effect in the VR measure was unrelated to participants' self-reported fear of spiders and stimulus evaluations. These results raise important implications about the usage of VR to study automatic behavioral tendencies.